Proceedings of the International Conference on Tourism, Economics, Accounting, Management, and Social Science (TEAMS 2018) 2019
DOI: 10.2991/teams-18.2019.35
|View full text |Cite
|
Sign up to set email alerts
|

The Firm Life Cycle Dynamics of Tax Avoidance

Abstract: This paper aimed at finding out whether tax avoidance differed across firm life cycle (FLC). We used cash flows pattern as a proxy to identify FLC into 4 phases, namely introduction, growth, mature, and decline. Tax avoidance was measured using effective tax rate (ETR) to show the impact of this practice on net income. Each FLC phase had different characteristics and hence explained its dynamics to implement tax avoidance in every stage. As a part of firms' important strategy, tax avoidance decision would cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
3
0
1
Order By: Relevance
“…Hasan et al (2017) implied that tax avoidance is positively related to the decline stage. The same results were found in the study of Mangoting and Onggara (2019). In addition, poor matching of revenues with expenses was found in the firms suffering a downturn.…”
Section: Theoretical Framework and Hypothesis Developmentsupporting
confidence: 84%
“…Hasan et al (2017) implied that tax avoidance is positively related to the decline stage. The same results were found in the study of Mangoting and Onggara (2019). In addition, poor matching of revenues with expenses was found in the firms suffering a downturn.…”
Section: Theoretical Framework and Hypothesis Developmentsupporting
confidence: 84%
“…According to their results, while tax avoidance is positively associated with introduction and decline stages, the authors observed a negative association with growth and mature stages when the shake-out stage is the benchmark. Mangoting and Onggara (2019) report similar results for tax avoidance and life-cycle stages. The authors state that tax avoidance is significantly positive in the introduction and decline stages and significantly negative in growth and mature stages.…”
Section: Theoretical Literature Reviewsupporting
confidence: 66%
“…Gross profitability is developing to a similar extent, which is the lowest in the early and ending stages of the life cycle. After reaching the top financial performance (at the stage of maturity) with maximum profitability, companies reduce the reported profit mainly for the purpose of tax avoidance in conflict with the results of Mangoting and Onggara (2018). Nevertheless, Drake (2015) argued in connection with this that mature companies have less persistent earnings and a higher difference between book and taxable income, which is reflected in downward earnings management.…”
Section: Univariate Analysismentioning
confidence: 99%